2010
DOI: 10.1074/jbc.m110.138198
|View full text |Cite
|
Sign up to set email alerts
|

A Ketone Ester Diet Increases Brain Malonyl-CoA and Uncoupling Proteins 4 and 5 while Decreasing Food Intake in the Normal Wistar Rat

Abstract: Three groups of male Wistar rats were pair fed NIH-31 diets for 14 days to which were added 30% of calories as corn starch, palm oil, or R-3-hydroxybutyrate-R-1,3-butanediol monoester (3HB-BD ester). On the 14th day, animal brains were removed by freeze-blowing, and brain metabolites measured. Animals fed the ketone ester diet had elevated mean blood ketone bodies of 3.5 mM and lowered plasma glucose, insulin, and leptin. Despite the decreased plasma leptin, feeding the ketone ester diet ad lib decreased volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
4
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 54 publications
(42 reference statements)
2
82
4
1
Order By: Relevance
“…Feeding the KME diet resulted in a signifi cant decrease in both L -glutamate and GABA. This observation provides additional support for the notion that the antiepileptic effect of KDs may result from the reduction in the excitatory amino acid glutamate associated with their use ( 77 ).…”
Section: Kessupporting
confidence: 56%
See 1 more Smart Citation
“…Feeding the KME diet resulted in a signifi cant decrease in both L -glutamate and GABA. This observation provides additional support for the notion that the antiepileptic effect of KDs may result from the reduction in the excitatory amino acid glutamate associated with their use ( 77 ).…”
Section: Kessupporting
confidence: 56%
“…Two KEs are known to be under current study: a ) 1,3-butanediol monoester of ␤ HB (KME) ( 77,(79)(80)(81)(82)(83)(84) and b ) 3GHB ( 48,85,86 ). Studies have demonstrated that orally or intravenously administered 1,3-butanediol or glycerol esters of ␤ HB are safe and well tolerated in animals ( 80,86 ), and that the orally administered 1,3-butanediol monoester is also safe and well tolerated in humans ( 79 ).…”
Section: Kesmentioning
confidence: 99%
“…A RAT LOWERS THE BLOOD GLUCOSE, WHILE AT THE SAME TIME LOWERING BLOOD INSULIN, DEMONSTRATING THAT KETOSIS INCREASES INSULIN SENSITIVITY Blood glucose decreased by about 50% from 5 to 2.8 mM while insulin decreased from 0.54 to 0.26 ng/ml in rats fed a diet where 30% of the calories from starch were replaced with ketone esters ( 20 ). Plasma leptin was also decreased from 3.12 to 1.83 ng/ml in rats, where ketone esters were substituted equi-calorically for starch.…”
Section: The Ketone Body D-␤ -Hydroxybutyrate Is a Natural Histone mentioning
confidence: 99%
“…Thus, acute infusion of 3HB into Langendorff-perfused rat hearts leads to a 25% increase in hydraulic work effi ciency of the heart ( 50 ) (36% when combined with insulin). Furthermore, very recent work shows that feeding mice a ketone ester diet affects both brown fat ( 51 ) and brain metabolism ( 52 ). Thus, the effects of Intralipid infusion that were previously ascribed to acute increases in lipids may in fact be due to increased ketone concentration.…”
Section: Discussionmentioning
confidence: 99%